Chelating properties of humic-like substances obtained from process water of hydrothermal carbonization - Santos, Vinicius S. [UNESP] (2021)
Recent studies have shown a new way of producing humic-like substances (HLS) from hydrochar prepared by hydrothermal carbonization of biomass. However, studies of HLS extracted from process water (PW) produced in hydrothermal carbonization process to the best of our knowledge are non-existent. In this work, hydrothermal carbonization of sugarcane bagasse and vinasse was performed under two concentrations of H2SO4 (1 and 4% w:w) followed of extraction of HLS from PW (HLS 1% and HLS 4%). The interaction of these compounds with Cu(II) ions revelated a complexation with high conditional stability constant (K ranged from 5.0 to 5.4) and high complexing capacity (CCc ranged from 3.1 to 3.9μmol mg−1). Elemental analysis and ash content showed that HLS 1% and HLS 4% both have high content of carbon, oxygen and inorganic compounds. In addition, the H/C molar ratio suggests that both HLS have aliphatic nature and O/C molar ratio acidic functional groups. FTIR analysis showed great variety of functional groups and also the presence of inorganic compounds. Excitation–Emission​ fluorescence matrices applied with complexation studies showed that interaction of HLS and Cu(II) occurs with two humic-like components. Data on Time Resolved Fluorescence Spectroscopy (TRFS) suggests that the mechanism of interaction between both HLS and Cu(II) occur by complexation. Furthermore, the infrared bidimensional analysis indicates that the binding sites for HLS 1% were in affinity order: COOCO > CH aliphatic, while for HLS 4% was: CH aliphatic > CO.